Impact of magnetic resonance imaging on functional integrity of non‐conditional cardiovascular implantable electronic devices. Issue 8 (24th June 2021) - Dahiya, Garima; Wetzel, Adam; Kyvernitakis, Andreas; Gevenosky, Loretta; Williams, Ronald; Shah, Moneal; Farah, Victor; Doyle, Mark; Biederman, Robert WW
Abstract: Background: Cardiovascular implantable electronic devices (CIEDs) have historically restricted the use of magnetic resonance imaging (MRI) due to the potential clinical and configurational risks associated with electromagnetic interference. In this study, the authors investigated the impact of MRI on the functional integrity of non‐conditional CIEDs and their clinical correlates. Methods: In this prospective, observational single‐center study, we enrolled patients undergoing MRI over a 5‐year period. Prior to assessing the impact of MRI on CIEDs, we performed interrogations in sequential duplication to assess the intrinsic variability of devices. Subsequently, we performed interrogations immediately after MRI, and monitored changes in device parameters and clinical events. Results: We completed 492 MRI studies, 58% in patients with permanent pacemakers (PPMs) and 42% with implantable cardioverter defibrillators (ICDs). Subsequent MRI exposures occurred in 15% encounters. Accounting for intrinsic variability in CIED leads, there were no significant changes in RA, RV, or LV parameters after MRI, regardless of the region imaged (thoracic vs. non‐thoracic), type of CIED (PPMs vs. ICDs) and among those with serial MRIs. When ranked for % change pre‐ to post‐MRI, the majority of RA, RV, and LV metrics for thresholds, sensing, and impedance conformed to ≤20% change from baseline. No significant clinical adverse cardiac events or effect on device microcircuitry occurred during the study. Conclusion: Incorporating a novel reproducibility tactic, there were neither clinically meaningful device parameter changes nor adverse clinical events during or following MRIs, suggesting the effects of MRI on non‐conditional CIED integrity are far less than previously perceived.